Assessing the Role of Continuing Education in Shaping Human Medicine, Dental Careers, and Pharmaceutical Jobs in the Era of Health Transformation: Systematic Review Based Findings - Keylani, Husain Abdullah; Alamrani, Saja Awad; Alshahrani, Mubarak Ali S.; Al-Hazmi, Shawgy Ibrahim; Fageehi, Nada Yousef Fageehi; Kuriri, Safieh Ahmad; Kareryi, Fatmah Ahmad; Anab, Najwa Ali; Kariri, Mansor Ali Mohammed; Ayashi, Mohammed Essa Safe; et al. (Journal of Posthumanism, 2025)
Background: Continuing professional development (CPD) plays a crucial role in ensuring that healthcare professionals maintain up-to-date knowledge and skills, particularly in the rapidly evolving fields of human medicine, dental careers, and pharmacy. However, disparities in CPD access and implementation across different regions, particularly in low- and middle-income countries (LMICs), present significant challenges to healthcare workforce development. Aim: This systematic review aimed to assess the role of CPD in enhancing professional competence, improving patient outcomes, and addressing the challenges in its implementation across human medicine, dental, and pharmaceutical sectors. Method: A systematic search was conducted for studies published between 2021 and 2025 in databases such as PubMed, Scopus, and Web of Science. Ten primary studies were selected based on their methodological rigor, focusing on CPD effectiveness, barriers to participation, and preferred learning modalities. Data were extracted and synthesized to identify trends and common themes. Results: The review found that CPD programs, particularly blended learning models, positively impacted professional competence and patient care outcomes. Barriers to CPD participation were most prevalent in LMICs, including resource constraints and limited access to digital platforms. Mandatory CPD systems were more effective in ensuring sustained participation and improving outcomes, while voluntary systems had lower engagement. Conclusion: CPD is essential for the continuous professional development of healthcare workers and the improvement of patient outcomes. However, addressing barriers to CPD participation, especially in LMICs, is critical to ensuring equitable access. Future research should focus on developing cost-effective, scalable CPD models to overcome these challenges.